Teachers’ Strategies and Challenges in Integrating Generative Artificial Intelligence into English Writing Instruction: A Systematic Review - Zuhriyah, Mukminatus (Corolla International Conference, 2025)
The researchers’ interest in exploring the benefits of integrating Generative Artificial Intelligence (GenAI), especially ChatGPT into English writing instruction has significantly increased. However, few review studies have explored the English teachers’ strategies and challenges in the ChatGPT integration into English writing instruction. Therefore, this systematic literature review (SLR) was conducted to describe the English teachers’ strategies and challenges in integrating ChatGPT into their writing classes. Using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), this study obtained 11 articles published in Scopus-indexed journals from January 2023 to July 2025 to be analyzed. The results reveal that eight ordered steps that the English teachers implemented and two types of English teachers’ challenges when integrating ChatGPT into English writing instruction. The findings can be a guide for English teachers to integrate ChatGPT into English writing instruction.